Misai kucing plotting arrangement under solar PV panel and harvester machine efficiency – a comparative study - Jamaludin, Muhamad Nurjafni; Mohd Basri, Mohd Salahuddin (Malaysian Society of Agricultural Engineers, 2019)
Orthosiphon stamineus, a member of the Lamiaceae, is a native plant to tropical Asia. Misai Kucing can be harvest four cycles per year after planting. In Malaysia, this plant has been planted under solar photovoltaic (PV) arrays in large scale area. Until today, the harvesting process of the shoot is done manually using regular hand cutters such as knife and scissors. It is difficult to harvest the shoots since there is limited space between the plant and the solar panels. By using machinery, the labor worker and overall cost can be reduced, and productivity and profitability can be increased. Prior to the harvesting machine development, a study on the plot arrangement of the Misai Kucing under PV panel is required. The objective of this study is to determine the best plot arrangement based on three parameters which are total polybag harvested, harvesting time required and distance covered by the machine under one PV panel. The results will be discussed in consideration with the efficiency aspect of the harvester machine. The result shows that the plot arrangement E which provide 4 polybags per row to be harvested at one time has the highest total polybag to time and distance ratio. This result provides efficiency for the harvester machine to be designed and developed.